The Role of Employees\' Wellbeing in Reducing the Effects of Work-Family Conflict on Family Satisfaction, Parenting Quality, and Couple Relationship Quality in Nurses - SMJ Mousavinia; A Naami; N Arshadi; K Beshlideh (Iran University of Medical Sciences, 2020)
Background & Aims: Today, work-family conflict is considered as one of the most important issues in the world of work, which is increasing rapidly and is not limited to one organization, and all organizations must pay special attention to this phenomenon in order to maintain their human resources as the most important competitive advantage. Nurses are no exception due to the high work requirements on the one hand and family issues on the other hand. People in the nursing profession usually work in different and sometimes irregular work shifts, and their work may be associated with stress and difficulties and affect nurses psychologically. In the meantime, the situation can be more difficult for married nurses, as they may become involved in work-family conflicts. The conflict between work and family as a major issue affecting both employees and employers and their families is accompanied by prominent family problems such as family satisfaction, couple relationship quality, and parenting quality. Therefore, industrial and organizational psychologists have focused their research on finding moderating variables to reduce such adverse effects. Therefore, the present study aimed to investigate the role of Wellbeing at Work in reducing the effect of work-family conflict on family satisfaction, couple relationship quality and parenting quality of nurses. Materia & Methods: The present study was a correlational survey. The research community consisted of married nurses with children of govermental Ahvaz city hospitals, among which 240 were selected as sample members in a multi - step sampling method. Thus, among the Governmental hospitals in Ahvaz, four hospitals were randomly selected and 5 wards were randomly selected from each hospital and 12 people from each ward were selected by simple random method as constituent members in The present study was considered. The data collection period was three months (from September to November 2019). Among the distributed questionnaires, 231 questionnaires were returned, of which 223 were fully completed and usable, and 8 questionnaires were incompletely completed and excluded from the analysis process. Criteria for inclusion in the study included marriage, having children, willingness and informed consent to participate in the research and complete answers to all questions of self-report questionnaires. Incomplete completion of the questionnaires was the exit criterion. Carlson et al. (2000) Work-Family Conflict, Aryee et al. (1999) Family Satisfaction, Chonody et al. (2016) Couple Relationship Quality, Arnol et al. (1993) Parenting scale, Zheng et al. (2015) Employee well‐being Scale were used for data collecting. Data analysis was performed using SPSS-16 software through descriptive statistics (mean, standard deviation, minimum and maximum) and inferential statistics (Pearson correlation and hierarchical regression). Results: The results of Pearson correlation coefficient showed that between work-family conflict and family satisfaction (r = -0/256, P <0/01), and Couple Relationship Quality (r = -0/274, P <0/01), and parenting quality ( r = 0/171, P <0/01), as well as between family-work conflict and family satisfaction (r = -0/273, P <0/01), and Couple Relationship Quality (r = -0/301, P <0/01), and Parenting quality (r = 0/165, P <0/01), there was a negative and significant relationship. Also, the results of hierarchical regression showed that adding the interaction of work-family conflict and Employeechr('39')s well-being to the regression equation in the second step, explained 0/631% of the variance of family satisfaction with 0/044% exclusive variance (𝜷= 0/227, P<0/01), and explained 0/685% of the variance of  the Couple Relationship Quality  increased by 0/022% of the exclusive variance (𝜷= 0/ 160, P<0/01), and the explanation of 0/671% of the variance of the parenting quality increased by 0/048% of the exclusive variance(𝜷= -0/237, P<0/01). Furthermore, the results of hierarchical regression showed that adding the interaction of family-work conflict and Employeechr('39')s well-being to the regression equation in the second step, explained 0/626% of the variance of family satisfaction with 0/036% exclusive variance (𝜷= 0/213, P<0/01), and explained 0/685% of the variance of  the Couple Relationship Quality increased by 0/016% of the exclusive variance (𝜷= 0/142, P<0/01), and the explanation of 0/654% of the variance of the parenting quality increased by 0/032% of the exclusive variance(𝜷= -0/200, P<0/01). Also, the regression coefficient related to the interaction of these variables showed that the interactive effect of work-family conflict and Employeechr('39')s well-being and also the interactive effect of family-work conflict and Employeechr('39')s well-being are statistically significant. Significance of this interaction means that the relationship between work-family conflict as well as family-work conflict with family satisfaction, the quality of couple relationship and the quality of parenting at high and low levels of Employeechr('39')s well-being are different. Therefore, it can be said that Employeechr('39')s well-being affects the relationship between work-family conflict and also family-work conflict with family satisfaction, the quality of couple relationship and the quality of parenting. Conclusion: The results indicate that work-family conflict as well as family-work conflict had a significant role in reducing family satisfaction, the quality of couple relationships and the quality of parenting in nurses. In explaining these findings, we can refer to the theory of spillover. Accordingly, onechr('39')s experiences in one area (work or life) leak into another. In addition, according to the theory of role, work and family are each separate areas and each area tries to spend more time and attention in society. Reducing time spent with family members due to attendance at work jeopardizes happiness and a sense of intimacy between them (time-based work-family conflict).On the other hand, not being on time at work due to family issues causes problems for the person in the organization (time-based family- work conflict). In addition, spending a lot of time, effort and attention in the workplace reduces a personchr('39')s energy to take care of the family (exhaustion-based work-family conflict). Conversely, spending too much time, effort, and attention on the family reduces a personchr('39')s energy to take on job responsibilities (exhaustion-based family- work conflict). The employee may also become so engrossed in the pursuit of resources in the workplace that he or she sees the home environment as an organization (behavior-based work-family conflict). Conversely, one may assimilate to onechr('39')s family roles to the extent that one performs appropriate behaviors with the family domain in the workenvironment (behavior-based family-work conflict). All of these factors can have a negative effect on family outcomes. In addition, regarding the moderating role of Employeechr('39')s well-being, the results of regression analysis showed that this variable can moderate the negative effects of conflicts between work and family on family satisfaction, the quality of couple relationships and the quality of parenting. To explaining these findings, it can be said that work-family conflict is described as an incompatibility between work and family roles, which arises from the incompatible pressure of family and job roles. In other words, when a person plays two or more roles that are incompatible with each other, he / she experiences role conflict. Everyone is affected by work and family issues, regardless of demographic characteristics, socioeconomic status or family structure. On the other hand, as stated in the definition of Employeechr('39')s well-being, Employeechr('39')s well-being in the form of experiences such as job satisfaction, job enthusiasm, independence, competence, self-acceptance, purposefulness, personal growth, positive relationships with others , And the absence of negative experiences such as anxiety, stress and depression in the workplace. In addition to providing the necessities of life, the job is directly related to the psychological well-being of the individual and also paves the way for the satisfaction of many of his/her immaterial needs.